2005
DOI: 10.1289/ehp.7989
|View full text |Cite
|
Sign up to set email alerts
|

Workgroup Report: Workshop on Source Apportionment of Particulate Matter Health Effects—Intercomparison of Results and Implications

Abstract: Although the association between exposure to ambient fine particulate matter with aerodynamic diameter < 2.5 μm (PM2.5) and human mortality is well established, the most responsible particle types/sources are not yet certain. In May 2003, the U.S. Environmental Protection Agency’s Particulate Matter Centers Program sponsored the Workshop on the Source Apportionment of PM Health Effects. The goal was to evaluate the consistency of the various source apportionment methods in assessing source contributions to dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 31 publications
5
95
0
Order By: Relevance
“…PM exposure to pollution from traffic sources often includes substantial secondary nitrates and coexposure to nitrogen dioxide and CO. Of course in most real-world environments, ambient PM pollution comes from many sources, including local and regional sources. Although the literature provides little evidence that a single source or well-defined combination of sources are responsible for the health effects, the relative importance of PM from various sources and the additive or synergistic effects of related copollutants remains a matter of debate 487,488 and will require substantial additional research.…”
Section: Relative Toxicity and Role Of Sources Andmentioning
confidence: 99%
“…PM exposure to pollution from traffic sources often includes substantial secondary nitrates and coexposure to nitrogen dioxide and CO. Of course in most real-world environments, ambient PM pollution comes from many sources, including local and regional sources. Although the literature provides little evidence that a single source or well-defined combination of sources are responsible for the health effects, the relative importance of PM from various sources and the additive or synergistic effects of related copollutants remains a matter of debate 487,488 and will require substantial additional research.…”
Section: Relative Toxicity and Role Of Sources Andmentioning
confidence: 99%
“…By comparing components of the factors with known source profiles, the factors can frequently be used as surrogates for source-related contributions to exposure. Using these techniques, studies have observed associations between sources of air pollution and several health effects, including mortality, Laden et al, 2000;Mar et al, 2000;Ozkaynak and Thurston, 1987;Thurston et al, 2005) cardiovascular and respiratory endpoints (Andersen et al, 2007;Lanki et al, 2006;Ostro et al, 2011;Sarnat et al, 2008), lung function decrements (Penttinen et al, 2006), low birth weight , and toxicological endpoints (Duvall et al, 2008;Maciejczyk et al, 2010;Seagrave et al, 2006;Zhang et al, 2008). More details on source apportionment results in air pollution health studies are reported by Stanek et al (2011).…”
Section: Statistical Techniques Used To Group Pollutantsmentioning
confidence: 99%
“…Since many approaches exist for developing source apportionment metrics, consistency among different techniques has been an area of active research (Hopke et al, 2006;Ito et al, 2006;Thurston et al, 2005;Viana et al, 2008). In studies comparing different receptor models, specifically PCA, FA, and PMF techniques, similar sources (and their corresponding mass) are generally identified when the same pollutant dataset is used (e.g., similar pollutant species from a similar location) (Hopke et al, 2006;Thurston et al, 2005).…”
Section: Statistical Techniques Used To Group Pollutantsmentioning
confidence: 99%
“…Laden et al (2000), applied factor analysis to the limited number of components of ambient PM that were measured in the Harvard Six Cities Study, and concluded that combustion-related PM 2.5 was the most closely associated measure with mortality. Other source apportionment-based health effects studies conducted in Washington, DC and Phoenix, AZ identified SO 4 ¼ as the PM index most closely associated with mortality (Thurston et al, 2005). Several time-series studies have examined PM and causespecific mortality, and impacts on susceptible subpopulations.…”
Section: Introductionmentioning
confidence: 99%